Do reservation wages react to regional unemployment? - Uwe Blien; Susanne Messmann; Mark Trappmann (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
Reservation wages indicate the wage threshold for which individual workers are inclined to supply their working capacity. In important theoretical approaches it is assumed that this threshold depends on the unemployment rate. If this is true, the variation of reservation wages might be an important force behind the regional wage curve, which has been estimated in many empirical studies. Up to now, the connection of regional unemployment with reservation wages has not been tested, since research possibilities depend on survey data which were not available. With the Labour Market and Social Security study (PASS), a new large panel survey in Germany, information on regional reservation wages is available. The empirical analysis with this data opens up the black box of the wage generation process and delivers insights about its determining factors. The analysis is based on job matching and efficiency wage theory which are used to derive a relationship between unemployment and reservation wages. – – Reservationslöhne bezeichnen die Schwelle, ab der Erwerbstätige bereit sind, ihre Arbeitskraft anzubieten. In einigen theoretischen Ansätzen wird angenommen, dass diese Schwelle von der Arbeitslosenquote abhängt. Wenn diese Annahme stimmt, kann die Variation von Reservationslöhnen ein wesentlicher Mechanismus für das Entstehen der Lohnkurve sein, die bereits in vielen empirischen Studien nachgewiesen wurde. Aufgrund der mangelnden Datenbasis konnte der Zusammenhang zwischen regionaler Arbeitslosigkeit und Reservationslöhnen bisher nicht geprüft werden. Mit dem 'Panel Arbeitsmarkt und soziale Sicherung' (PASS), einer neuen großen Panelstudie in Deutschland, sind nun Informationen zu regionalen Reservationslöhnen verfügbar. Die empirische Analyse dieser Daten eröffnet nunmehr den Blick in die Black Box des Lohnentstehungsprozesses und ermöglicht Einsichten in dessen Determinanten. Der Artikel verwendet die Job-Matching- und die Effizienzlohntheorie, um erwartete Zusammenhänge zwischen Arbeitslosigkeit und Reservationslöhnen abzuleiten.
Keywords: J64; J31; R23; 330; Reservation Wages; Wage Curve; Regional Labour Markets; Anspruchslohn; Regionale Arbeitslosigkeit; Lohnkurve; Deutschland